The perception of Kuala Lumpur publics' on tree retention and urban development - Mohd Hisyam, Nor Hanisah; Hitchmough, J. D.; Muda, A. (Elsevier, 2012)
Massive urban land conversion has led to the urgent need to retain and conserve trees. This study attempted to assess the local publics’ perceptions on trees in the context of tree retention and urban development. The data collected regarding respondents’ gender, age, ethnicity, educational attainment and occupation were tested. Mix responses were received from the public where monetary value statement received the least significant result. In conclusion, Kuala Lumpur publics support the idea of retaining trees in urban areas. City Hall of Kuala Lumpur should emphasized a comprehensive planning and retaining trees within the jurisdiction by collaborating with the private agencies and non- governmental organizations.